ANALISIS STRUKTUR TIANG PANCANG (PILE) PIPA BAJA KOMPOSIT PELABUHAN BONGKAR MUAT SEBAWANG - Susanto, Azis; Ramadan, Yudis (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
ABSTRACT: Tana Tidung Regency as a coastal area, is in dire need of sea transportation to open remote and isolated areas and to increase the economy, so that it will improve the standard of living, especially for the people of Tana Tidung Regency. Therefore, the Tana Tidung Regency government plans to build a Loading and Unloading Dock in Sebawang, Sesayap Hilir District. This research is to provide an alternative pile structure that can be used as a safe and efficient structure for Loading and Unloading Sebawang Port. From the results of land surveys and investigations, the planned location of the port area has a river contour and a hard soil layer that is sufficiently deep so that adequate piles are needed. The results of analysis using D-80 steel pipe pile (Grade 2) 12.7 mm thick over stressed in the style of 2705.72 kN in the dock pile structure, so that it was re-analyzed using composite steel pipes with K-250 reinforced concrete filling (8D16 ) The results of the composite axial steel analysis increased to 5571.48 kN, making it safe to use. Keywords: Pile, Steel Pipe, Composite ABSTRAK: Kabupaten Tana Tidung sebagai daerah pesisir, sangat memerlukan transportasi laut untuk membuka daerah-daerah terpencil dan terisoler serta untuk meningkatkan roda perekonomian, sehingga akan meningkatkan taraf hidup khususnya masyarakat Kabupaten Tana Tidung. Oleh karena itu pemerintah Kabupaten Tana Tidung berencana membangun Dermaga Bongkar Muat di Sebawang Kecamatan Sesayap Hilir. Penelitian ini untuk memberikan alternative struktur tiang pancang yang dapat digunakaan sebagai struktur Pelabuhan Bongkar Muat Sebawang yang Aman dan efesien. Dari hasil survey dan penyelidikan tanah, area lokasi rencana pelabuhan memiliki kontur sungai dan lapisan tanah keras yang cukup dalam sehingga diperlukan tiang pancang yang memadai. Hasil analisis menggunakan tiang pancang pipa baja D-80 (grade 2) tebal 12,7 mm mengalami over stressed pada gaya 2705,72 kN di struktur tiang pancang dermaga, sehingga dianalisis kembali menggunakan pipa baja komposit dengan isian beton bertulang K-250 (8D16). Hasil analisis gaya aksial baja komposit tersebut meningkat menjadi 5571,48 kN, sehingga aman untuk digunakan.Kata kunci: Tiang Pancang, Pipa Baja, Komposit